A Case of DeSanto-Shinawi Syndrome in Bahrain with a Novel Mutation - Zahra Alsahlawi; Mohamed Jailani; Husain Alaradi; Abdulaziz AlAbbad (Case Reports in Pediatrics)
DeSanto-Shinawi syndrome is a rare genetic condition caused by loss-of-function mutation in WAC. It is characterized by dysmorphic features, intellectual disability, and behavioral abnormalities. In this case report, we describe the clinical features and genotype of a patient with a novel mutation 1346C > A in WAC. This patient’s dysmorphic features include a prominent forehead, bulbous nasal tip, macroglossia, deep-set eyes, and malar hypoplasia. This patient also showed signs of intellectual disability and behavioral abnormalities such as night terrors. These findings are consistent with those described in earlier reports. Here, we report new findings of epilepsy and recurrent skin infections which had not been reported in prior studies.